All the little bird-hearts - Lloyd-Barlow, Viktoria, 1974- (Algonquin Books of Chapel Hill, 2023)
"Sunday Forrester lives with her sixteen-year-old daughter, Dolly, in the house she grew up in. She does things more carefully than most people. On quiet days, she must eat only white foods. Her etiquette handbook guides her through confusing social situations, and to escape, she turns to her treasury of Sicilian folklore. The one thing very much out of her control is clever headstrong Dolly, now on the cusp of leaving home"--